Regulating Dark Patterns in Indonesian E-Commerce: Comparative Lessons from South Korea and the EU - Az-Zahra’, Putri Nabila; Nurlaily, Nurlaily; Agustianto, Agustianto (Journal of Judicial Review, 2025)
The proliferation of dark patterns, which are manipulative interface designs that influence user decisions, poses a major legal challenge in e-commerce by compromising consumer autonomy. However, existing Indonesian legal instruments (Consumer Protection Law, the amended EIT Law, and the Personal Data Protection Law) do not explicitly address them. The core legal issue lies in the absence of clear legal provisions, definitions, and enforcement mechanisms governing dark patterns in Indonesia’s digital marketplace. This study aims to evaluate the regulatory gaps in Indonesia's consumer protection framework by comparing it with more advanced legal systems in South Korea and the European Union. Employing a normative legal research method and a comparative-legal approach, the study analyzes legal texts and institutional mechanisms from all three jurisdictions. The findings indicate three regulatory gaps in Indonesia: the lack of explicit substantive prohibitions, the absence of specialized institutional oversight, and the unavailability of technical guidelines for digital interface governance. In contrast, South Korea regulates five categories of dark patterns through its E-Commerce Act and enforces compliance through the Korea Fair Trade Commission, while the European Union explicitly prohibits deceptive design practices under the Digital Service Act, supported by the UCPD, GDPR, and the EDPB Guidelines. These comparative insights indicate that Indonesia’s reactive regulatory posture fails to reflect the ideals of justice, legal certainty, and social utility as articulated by Gustav Radbruch. Academically, this study contributes by offering a structured three-pillar framework: substantive norms, institutional strengthening, and technical guidelines, as a foundation for developing a more adaptive and consumer-centered digital regulatory system. To remedy this, the study recommends adopting a progressive legal strategy inspired by Satjipto Rahardjo, involving explicit statutory definitions, institutional reforms, and technical instruments such as interface ethics guidelines and integrated digital dispute resolution systems.